2020
DOI: 10.1101/2020.04.20.050211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defective membrane repair machinery impairs survival of invasive cancer cells

Abstract: Cancer cells are able to reach distant tissues by migration and invasion processes. This study shows that inhibition of the plasma membrane repair machinery may represent a promising avenue for annihilating cancer metastasis. AbstractCancer cells are able to reach distant tissues by migration and invasion processes. Enhanced ability to cope with physical stresses leading to cell membrane damages may offer to cancer cells high survival rate during metastasis. Consequently, down-regulation of the membrane repair… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Sarcolemma repair assay was performed by laser ablation in the presence of Ca 2+ and FM1-43, as previously described [ 32 , 33 ]. By analyzing changes in the FM1-43 intracellular fluorescence intensity, we first confirmed that LHCN myotubes are able to reseal a µm-size membrane damage in about 80 s ( Figure 2 A,C) as previously reported [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcolemma repair assay was performed by laser ablation in the presence of Ca 2+ and FM1-43, as previously described [ 32 , 33 ]. By analyzing changes in the FM1-43 intracellular fluorescence intensity, we first confirmed that LHCN myotubes are able to reseal a µm-size membrane damage in about 80 s ( Figure 2 A,C) as previously reported [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Membrane repair was assayed as recently reported [ 32 ], according to a protocol that differed slightly from our previous studies [ 26 , 33 ]. Myotubes were cultured in complete growth medium on 18*18-mm glass coverslips (Nunc).…”
Section: Methodsmentioning
confidence: 99%
“…This allows us to test the cellular response to PM ruptures of nanoscopic dimensions in both cells and model membranes. Nanoscopic holes may be frequent during aggressive cellular migration and invasion 1,17 and therefore investigation of protein recruitment in response to nanoscopic ruptures are relevant for understanding how living cells cope with ruptures.…”
Section: Resultsmentioning
confidence: 99%
“…This study echoes a work which demonstrates that during the migration along type I collagen fibers, MDA-MB-231 cells undergo membrane damage during this process. These membrane lesions are repaired by the concomitant action of annexins 5 and 6 49 . One hypothesis is that these tracks could originate from membrane lesions due to a too strong adhesion to the matrix during tumor cell migration.…”
Section: Discussionmentioning
confidence: 99%